Relação professor-aluno: os efeitos da afetividade na aprendizagem dos alunos dos anos iniciais do ensino fundamental - Silva, Julia Costa (Universidade Federal de São Carlos, 2025)
This qualitative, literature-based research aimed to identify and analyze what academic publications from 2015 to 2025 reveal about the effects of the teacher-student relationship on the learning process in the early years of elementary education. Three scientific articles available in the CAPES and SciELO databases were selected based on thematic and temporal criteria. The analysis was guided by the theoretical contributions of Henri Wallon, Lev Vygotsky, and Paulo Freire, who recognize affectivity as a fundamental dimension of education. The findings indicate that positive affective bonds between teachers and students foster not only student engagement and motivation, but also improvements in classroom behavior and academic performance. The analyzed studies emphasize that active listening, mutual respect, and the recognition of the student as a subject contribute to building a more meaningful school environment, where learning is closely linked to emotional and social development. Furthermore, the presence of humanized relationships in school supports the development of cognitive, emotional, and social skills, highlighting the importance of empathetic and sensitive pedagogical mediation. The research also identified a significant limitation: the scarcity of studies directly addressing the teacher-student relationship in the early years of elementary school, particularly in the Brazilian context. This gap points to the need for further research aimed at deepening the understanding of this topic and proposing strategies to strengthen such relationships. It is concluded that affective bonds in school should be understood as a fundamental pillar for promoting a more welcoming, critical, and transformative education, committed to the holistic development of children.
Teacher-student relationship: the effects of affectivity on the learning process of early elementary school students
Keywords: Anos iniciais do Ensino Fundamental; Afetividade na Educação; Relação professor-aluno; CIENCIAS HUMANAS::EDUCACAO